Enzyme Efficacy of Aero - contaminated Digestive Syrups - Kulkarni N. S.; Bodhankar M. G.; Ansingkar S. S.; Dalal J. M. (International Journal of Research in Chemistry and Environment (IJRCE), 2011)
Airborne microbial contamination may affect the functional properties of enzyme in digestive syrups. Present investigation was carried to assess the a-amylase activity of aerocontaminated digestive syrups. The protein content along with enzyme activity of digestive syrups challenged with environmental isolates of proteolytic aero flora. The results obtained show considerable reduction in the efficacy of an enzyme activity indicates the need for post selling quality management of pharmaceutical products.